TECHNOLOGICAL INNOVATION FOR SUSTAINABILITY: ENCOURAGING ECONOMIC GROWTH IN THE DIGITAL ERA - Tarishah Hatim Faqih; Rizqy Fadhlina Putri; Ratna Sari Dewi; Asni Septiana; Azhari Wijaya (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In today's digital age, technology has become a crucial factor in increasing economic growth. This article comprehensively discusses the relationship between technology and innovation. Affecting the economy in the digital era, it also touches on the challenges and opportunities involved. By referring to the results of the literature review, this article has identified that information and communication technology (ICT), such as technologies such as the internet, cloud computing, big data, artificial intelligence (AI), and the Internet of Things (IoT) have changed business and economic work patterns. The importance of technology in driving economic growth is very evident through the endogenous growth theory which highlights the importance of investment in research and development and innovation as a key factor. The impact of technology on productivity, efficiency, and economic competitiveness is increasingly visible through its application in various industrial sectors. The role of open collaboration and innovation is vital in accelerating technological progress, while providing guidance on how to design policies that support economic growth. Inclusive and sustainable development in the digital era. In addition, this article also explores the problems faced, such as digital inequality and the need for regulations that can adapt. Drawing on a literature review, this article investigates that technology and innovation are key to achieving sustainable and inclusive economic growth in the digital age.